Open-heart surgery in preterm infants: A single-center experience - Danish Memon; Praveen Reddy Bayya; Perraju Bendapudi; Jessin Puliparambil Jayashankar; Brijesh Parayaru Kottayil; Balaji Srimurugan; Raman Krishna Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Open-heart surgery is challenging in preterm neonates and infants, and its feasibility in low-resource settings has not been defined. We describe our institutional experience with open-heart surgeries performed on consecutive preterm infants. Materials, Methods and Results: This was a single-center retrospective cohort from a tertiary hospital in Southern India and included consecutive preterm neonates (<37 weeks) admitted for open-heart surgery. This report is limited to babies who were <3 months at the surgery. The salient features of the 15 preterm included twin gestation: 7 (46.7%); median gestational age at birth: 35 weeks (28-36 weeks); median corrected gestational age at surgery: 37 weeks (33-40 weeks); birth weight: 1.75 kg (1.0-2.6 kg); weight at surgery: 1.8 kg (1.2-2.9 kg); and small for gestational age: 12 (80%). The heart defects included transposition of the great arteries (7), total anomalous pulmonary venous return (3), large ventricular septal defect (VSD) (1), and VSD with coarctation of the aorta (4). Eleven (73%) were mechanically ventilated preoperatively and five had preoperative sepsis. The mean cardiopulmonary bypass time was 169.7 ± 61.5 min, and cross-clamp time was 99.7 ± 43.8 min. There was no inhospital mortality; one baby expired during follow-up at 1 month. Postoperative mechanical ventilation duration was 126.50 h (84.25-231.50 h), and intensive care unit stay was 13.5 days (9-20.8). The total hospital stay was 39 days (11-95 days). Two children (13.3%) had postoperative sepsis. Conclusion: Through collaborative multidisciplinary management, excellent outcomes are feasible in low-resource environments for selected preterm neonates undergoing corrective open-heart operations.